Pomiar jakości usług motoryzacyjnych metodą SERVQUAL - Radkowska, Jolanta; Radkowski, Krzysztof (Measurement of Motor Services Quality Applying SERVQUAL Method, 2006)
The problem of quality service is one of common topics of discussion among economic theorists and practitioners. This probably results from the problems faced by many service providers trying hard to satisfy customers. One of the essential problems in researching service quality is determining the variable influences on the quality of service from the customer's point of view as well as the means of measuring the value of such variables. Considering the virtues of the method of SERVQUAL, it is the adapted and applied model to identify quality of motor services, as well as to establish the customer's hierarchy of importance relating to variables determining the quality of motor services.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 575-584